Konsep Murabahah Ibnu Rusyd dan Implementasinya pada Bank Syariah di Indonesia - Mahmudi, Muhammad Aly; Masyhadi, Ahmad; Syaputra, Muhammad Alvan (Al-Faruq: Jurnal Hukum Ekonomi Syariah dan Hukum Islam, 2022)
Murabahah are one of the products of Islamic banks. In addition to this concept being similar to credit transactions in conventional banks, this concept becomes dilemmatic when legality is found to be facilitated by the DSN-MUI, which in its consideration also quotes from the work of Ibn Rusyd. Murabahah was identified as having similarities with the credit system in the concept of borrowing for certain purchases with a return of more than the loan called profit or an additional from the initial price in the installment according to the customer's ability which of course is in accordance with the agreement between the bank and the customer. This research seeks to reveal: first, whether the murabahah contract is in accordance with the valid muamalah contract. Second, to reveal the legality of the murabahah contract in the concept of Ibn Rusyd with the reality of its application to Islamic banks in Indonesia. This type of research is library research that uses a descriptive-qualitative method, by collecting library data, reading, and recording and processing research materials. This research resulted in a conclusion: first, the murabahah contract is valid if the goods sold belong to the bank in principle and no element of fraud or loss from one of the parties is found. Second, the concept of Ibnu Rusyd is in accordance with one of the forms of murabahah applied to Islamic banks in Indonesia if the initial price determination of the agreed price is either with additional or not and the implementation of installment payments according to the agreed period and benefits.